Beyond market failures: the market creating and shaping roles of state investment banks. Issue 4 (1st October 2016) - Mazzucato, Mariana; Penna, Caetano C.R.
Abstract : The paper develops a typological framework of the roles of state investment banks (SIBs) in the economy. The typology identifies four different roles: countercyclical; developmental; venture capitalist; and challenge-led. The paper conceptually elaborates the typology by first providing a historical overview of SIBs, and then discussing how the mainstream "market failure theory" justifies them. It then advances a different conceptualization based on insights from heterodox economics, showing that all roles of SIBs are more about market creating/shaping rather than market-failure fixing. The paper concludes with a proposal of a new agenda for research on SIBs based on our typological framework.